LA SOCIOLOGIA DELLA MEMORIA IN MAURICE HALBWACHS - Montesperelli, Paolo (Aurora. Revista de Arte, Mídia e Política, 2011)
Maurice Halbwachs inspires himself to the concept of “collective representation” (Durkheim) in order to define her concept of “collective memory”: ones recollection is never just individual as it is created inside the society and is evoked as a consequence of social interaction. That which is remembered isn’t just secured in the memory, it isn’t merely an image of the past; it is a clue, a trace of the past that has to be interpreted in the present in order to give a meaning to the present itself. The criticisms that have been directed against Halbwachs don’t invalidate his actuality, that regarded various aspects, methodological and theoretical: the consonance with social history, the methodological problem of the sources of information and especially the importance that he gives to the meanings, following a prospective similar to the social phenomenology. But his actuality regards also the developments of the concept of “objective spirit” and the importance given to time, that link this author to contemporary hermeneutics.